Residue dissipation kinetics and consumer risk assessment of tebuconazole in tomato fruits and the soil - Majumder, Sujan; Kumar, Ratendra; Abhinay; Patel, Ajeet Kumar; Pandey, Koshlendra Kumar; Singh, Arvind Nath; Behera, Tusar Kanti (Vegetable Science, 2024)
Tebuconazole residue in tomato fruit and soil was estimated using gas chromatography equipped with a microelectron capture detector (μECD, 63Ni) and the analytical method was validated. The percent recovery at 0.01, 0.02, 0.05, 0.10 and 0.50 mgkg-1 was 85.00 to 94.00% in tomato and 81.67 to 89.67% in soil. Tebuconazole is used to control early blight, late blight and powdery mildew. Its residues may remain in the crops, causing the health hazard. Thus, analysis of tebuconazole residue, its dissipation rate and safety evaluations in tomatoes were studied using the validated method. The dissipation of tebuconazole was studied in two doses, i.e., single dose (SD) and double doses (DD). Residues were extracted from tomato fruit with ethyl acetate, and cleanup was given using primary secondary amine (PSA) and magnesium sulfate. The half-life was 3.75 and 1.35 days for SD and DD, respectively. Dietary exposures of the residues were less than MPI of 0.48 mg person-1 day-1 on all the sampling days for both doses. The terminal residue in the soil was found below LOQ for both doses.